The role of social protection in improving child well-being and care in Africa - Roelen, Keetie (International Food Policy Research Institute, 2018)
This chapter aims to provide an overview of the role of social protection in improving child well-being and care in Africa by considering progress made and gaps to be addressed. First, it reflects on coverage, highlighting the rapid expansion of social protection and reflecting on undercoverage among particular groups of children. Second, it provides an overview of the impact of social protection on children, considering direct and indirect income effects, psychosocial and behavioral effects, and structural constraints. Third, it offers reflections on the way forward, particularly in relation to the design and implementation of programs. Note that this chapter focuses primarily on social assistance, referring to interventions that offer cash or in-kind support on a noncontributory basis.